МІЖНАРОДНІ СТАНДАРТИ ЗДІЙСНЕННЯ АДМІНІСТРАТИВНОГО СУДОЧИНСТВА УКРАЇНИ: СУТНІСТЬ ТА КЛАСИФІКАЦІЯ - Ославський, Михайло Іванович (SUPREMANCE OF LAW, 2019)
The article is devoted to the research of the concept and content of international standards of the administrative legal proceedings. The theoretical and methodological specificity of the research of the concept and content of international legal standards is that the legal standards of any sphere can not be considered in isolation from the development of the entire legal system, all its sectoral and institutional elements. However, any international standards have a relatively independent nature: they are formed in a specific legal system, due by the development of this system and a special tool for «sectoral» purposes. The legal standard is considered as a particular sample (etalon, model), taken as output to compare with other similar objects or phenomena. This is a set of uniform, typical principles and rules of conduct of subjects of law, reflected in sources of law. Under the standards of administrative legal proceedings it is necessary to understand the system of legal models, norms, principles and legal practices, that establish the obligatory (minimum) level of assurance of the rights of a person in the administrative proceedings and ways to exercise of such rights. Th e variants of classifi cation of the system of such standards are revealed and its signifi cance for its correct application is determined. On their basis, generally accepted international standards for administrative proceedings are proposed to be divided into two general groups: 1) international standards, which contained in normative acts of a universal nature; 2) generally accepted European standards - international standards, which enshrined in European international legal acts. The significance of international standards of administrative legal proceedings for the process of harmonization of Ukrainian legislation with the European Union law is substantiated. Compliance with the requirements of international normative legal acts in the sphere of administrative legal proceedings is considered as an important aspect of the state policy of Ukraine in the sphere of integration into the European and international community.
Keywords: international standards; European standards; international legal act; administrative proceedings; administrative court